High resolution chromatography : a practical approach - Millner, P. A (Oxford University Press, 1999)
Researchers attempting to isolate and purify proteins rely on chromatography. This volume provides quick access to both new chromatographic techniques and improvements in traditional methods.
Practical approach series ; 204
Keywords: biologie; Chromatography, Affinity; chromatografie afinitní; nukleotidy; biomedicínské inženýrství; Nucleotides